2021
DOI: 10.1101/2021.12.28.474333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 vaccination induces immunological memory able to cross-recognize variants from Alpha to Omicron

Abstract: SUMMARYWe address whether T cell responses induced by different vaccine platforms (mRNA-1273, BNT162b2, Ad26.COV2.S, NVX-CoV2373) cross-recognize SARS-CoV-2 variants. Preservation of at least 83% and 85% for CD4+ and CD8+ T cell responses was found, respectively, regardless of vaccine platform or variants analyzed. By contrast, highly significant decreases were observed for memory B cell and neutralizing antibody recognition of variants. Bioinformatic analyses showed full conservation of 91% and 94% of class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 44 publications
5
38
0
1
Order By: Relevance
“…However, when considering the overall response to Spike, we found that the majority of the response is conserved. Our observations are in agreement with works from other groups recently released as pre-print publications, which suggest minimal escape of T cell immunity by Omicron ( 21 26 ). Although it may not be sufficient alone to guarantee protection from infection, a conserved CD4+ T cell immunity against common SARS-CoV-2 VOCs may be fundamental to reduce disease severity, as demonstrated by the importance of a rapid T cell response in preventing severe COVID-19 ( 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, when considering the overall response to Spike, we found that the majority of the response is conserved. Our observations are in agreement with works from other groups recently released as pre-print publications, which suggest minimal escape of T cell immunity by Omicron ( 21 26 ). Although it may not be sufficient alone to guarantee protection from infection, a conserved CD4+ T cell immunity against common SARS-CoV-2 VOCs may be fundamental to reduce disease severity, as demonstrated by the importance of a rapid T cell response in preventing severe COVID-19 ( 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, confirmation of our results from cohorts in other geographical areas and exposure to other vaccines would offer further reassurance of the maintenance of T cell responses against Omicron. Indeed, emerging data suggest this to be the case 25,[41][42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is supported by two recent preprint publications indicating that the majority of the T-cell response induced by vaccination or natural infection cross-recognizes the Omicron variant, thereby likely contributing to protection against severe disease. 20,21 An alternative or additional mechanism by which protection against severe disease may be conferred, despite reduced neutralizing antibody activity against the Omicron variant, is through Fc-mediated effector functions of non-neutralizing antibodies inducing antibody-mediated cellular phagocytosis, complement deposition, and natural killer cell activation. 18,22 In addition, the Omicron variant may be less potent at causing serious illness.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the extent to which the polyepitopic T-cell response induced by vaccination against the spike-protein and the even more diverse polyepitopic T-cell response stimulated by natural infection, with or without vaccination, remain cross-reactive against the Omicron variant warrants further investigation. 20,21…”
Section: Discussionmentioning
confidence: 99%